German medical data sciences: Bringing data to life: Proceedings of the joint annual meeting of the German association of medical informatics, biometry and epidemiology (GMDS e.V.) and the Central European Network - International Biometric Society (CEN-IBS) 2020 in Berlin, Germany - Röhrig, Rainer; Beißbarth, Tim; Brannath, Werner; Prokosch, Hans-Ulrich; Schmidtmann, Irene; Stolpe, Susanne; Zapf, Antonia (IOS Press, 2021)
The COVID-19 pandemic has brought into sharp focus the need for the collection of data. Such data cannot be collected or provided without medical informatics, documentation and health data management. Nor can health data be evaluated and converted into a useful tool for making the important decisions that affect us all without biometrics and epidemiology, bioinformatics and systems biology. This book presents full papers from GMDS & CEN-IBS 2020, the first joint online conference of the German Association of Medical Informatics, Biometry and Epidemiology (GMDS) and the Central European Network & the International Biometric Society (CEN-IBS), held online between 6 and 11 September 2020. The title of the conference was Bringing Data to Life, a reference to the increasing amount of data in medical research which is inextricably related to the fast-developing digitalization of the health system. Many challenges must be addressed in order to make use of and benefit from these increasing sources of data, and these can only be faced if all disciplines related to data science work together. The conference aimed to bring together the diverse disciplines within data science, including medical informatics, bioinformatics, biostatistics, epidemiology, public health and medical documentation. Topics covered in the book include central themes relevant to society in general and advances in data technology which support innovations in medical research in particular. The book brings together many topics related to the provision and analysis of data in medicine, and will be of interest to all those working in the field.
CRIS-Team Scopus Importer:2021-10-15